Ana Ürrütiren "Ebanjelio Saintia Jesus-Kristena Jondane Johaneren arabera" (1873) - Padilla Moyano, Manuel (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2025)
Lan honetan Ana Ürrüti ebanjelista eta idazle zuberotarraren testu nagusiaren edizio kritikoa eskaintzen da. Alderdi biografiko eta bibliografikoen ondoren, Ebanjelio Saintiaren sorrera azalduko da, itzulpenaren iturrien aniztasuna agerian utzirik ere. Edizio kritikoa 1873ko eta 1888ko edizioen ale banaren transkripzioan oinarritzen da. Bi argitaraldi horietan atzeman diren akatsak zuzendurik, irakurleari eskaintzen zaion bertsioak testu originala berreraiki nahi du. Harago, Ana Ürrüti andereari aitortza ematea da lan honen azken xedea. This paper presents a critical edition of the translation into Souletin Basque of the Gospel of John by Anna Urruty, an evangelist and writer from the Country of Soule. After biographical and bibliographical aspects, the genesis of Urruty’s Ebanjelio Saintia will be explained, and the diversity of sources for the translation revealed. Our critical edition starts from the transcription of two exemplars of the 1873 and 1888 editions. The version offered to the reader attempts to reconstruct the original text by correcting the errors detected in those two editions. Ultimately, this work is a tribute to the extraordinary figure of Anna Urruty. This paper presents a critical edition of the translation into Souletin Basque of the Gospel of John by Anna Urruty, an evangelist and writer from the Country of Soule. After biographical and bibliographical aspects, the genesis of Urruty’s Ebanjelio Saintia will be explained, and the diversity of sources for the translation revealed. Our critical edition starts from the transcription of two exemplars of the 1873 and 1888 editions. The version offered to the reader attempts to reconstruct the original text by correcting the errors detected in those two editions. Ultimately, this work is a tribute to the extraordinary figure of Anna Urruty.